Efficient Camera Pose Adjustment to a Mirror Array for Structured Light Field Video Acquisition - Maeda, Shunsuke; Kodama, Kazuya; Hamamoto, Takayuki (Visual communications and image processing (Online), 2024)
We previously implemented an inexpensive imaging system that combines a single real camera with a mirror array located along a paraboloid. It allows us to robustly acquire dynamic light fields composed of multi-view videos by providing a virtual camera array, where its viewpoints exist in the mirrors. Actually, as moving the real camera to the focus of the paraboloid, virtual viewpoints in the mirrors get equally-spaced to achieve multi-view imaging with structured disparity. In this paper, we discuss an efficient method for adjusting the pose of a single camera to acquire high quality dynamic light fields as multi-view videos. Specifically, we introduce some indicator values determined by detected corners of the mirror array on acquired images while adjusting the camera. By using these values for camera adjustment, we easily know how to move its position and virtually correct its angle through homography transform. Experimental results of simulations demonstrate that our proposed method sufficiently achieves structured light field video acquisition with equally-spaced virtual viewpoints, where we do not need camera rotation requiring complex devices and only the camera position is controlled by a simple 3D system like XYZ stages.